PERBATASAN INDONESIA-MALAYSIA DI PULAU SEBATIK TERHADAP KONDISI SOSIAL DAN EKONOMI MASYARAKAT LOKAL - Bani, Ferdinandus; Katoda, Ignecya Thithania; Sanam, Marcos S. Y.; Wage, Guido Tobhi; Arman, Yohanes (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
The border dispute between Indonesia and Malaysia on Sebatik Island has a significant impact on the social and economic life of the local community. Sebatik Island, which is divided between the two countries, creates complex dynamics due to political tensions and differences in policies. Communities on both sides of the border often have strong family ties, but legal uncertainty and mobility restrictions disrupt their social interactions. Limited basic infrastructure and poor access to education worsen economic conditions, increasing the community's dependence on the economy on the Malaysian side. This study uses a qualitative method with a case study approach to explore the impact of the border dispute on the local community and identify obstacles to infrastructure development. Efforts to resolve the dispute are needed, involving dialogue, local wisdom, and infrastructure improvements to improve the welfare of the community on Sebatik Island.